Ten beautiful things - Griffin, Molly Beth (Charlesbridge, 2021)
Lily is moving into her grandmother's farm in Iowa, and she is sad about all the changes necessary in her life--but on the long drive her grandmother challenges her to find ten beautiful things that they can share together.